Capital flows and private investment in Mexico - Carlos A. Ibarra (Centro de Investigación y Docencia Económicas, A.C., 2013)
Based on the so-called bounds testing approach, the paper studies the long-run effect of capital flows and the real exchange rate on Mexicos private in- vestment from 1988 through 2008, presenting two main results. First, while capi- tal inflows can potentially increase investment, in practice they may lower it, be- cause, as capital flows in, the peso appreciates. Second, although both fdi and portfolio inflows can increase investment, the effect from fdi is significantly small- er in contrast to a frequent finding in the literature for other countries. Both results help to explain the low transfer of capital flows to investment in Mexico, and more generally the low levels of investment observed in the country.